2016
DOI: 10.3389/fmicb.2016.01746
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Silver Nanoparticles Produced by Bacillus pumilus As Antimicrobial and Nematicide

Abstract: This study evaluates the potential application of silver nanoparticles (AgNPs) as antimicrobial or nematicidal agents produced by the extremophile Bacillus pumilus, which was isolated from the alkaline Wadi El-Natrun Lake in Egypt. The AgNPs were characterized by ultraviolet–visible absorption spectroscopy, transmission electron microscopy, and energy dispersive x-ray spectroscopy. The size of AgNPs formed ranged from 20.12 to 29.48 nm. Panagrellus redivivus was exposed to different concentrations (0, 50, 100,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 45 publications
1
30
1
Order By: Relevance
“…Silver nanoparticles synthesized by Bacillus pumilus possess potent antimicrobial activity against different Gram‐positive and Gram‐negative human pathogenic bacteria, including methicillin‐resistant Staphylococcus aureus , Staphylococcus epidermidis , Streptococcus bovis , E. coli , P. aeruginosa , Shigella sonnei , Klebsiella pneumoniae , and Salmonella typhimurium . [ 306 ] Fungi produce enzymes that act as both reducing and capping agents to produce stable and shape‐controlled AgNPs. [ 307 ]…”
Section: Applicationsmentioning
confidence: 99%
“…Silver nanoparticles synthesized by Bacillus pumilus possess potent antimicrobial activity against different Gram‐positive and Gram‐negative human pathogenic bacteria, including methicillin‐resistant Staphylococcus aureus , Staphylococcus epidermidis , Streptococcus bovis , E. coli , P. aeruginosa , Shigella sonnei , Klebsiella pneumoniae , and Salmonella typhimurium . [ 306 ] Fungi produce enzymes that act as both reducing and capping agents to produce stable and shape‐controlled AgNPs. [ 307 ]…”
Section: Applicationsmentioning
confidence: 99%
“…The variability in the lethal concentrations in these studies may be attributed to procedural differences in preparation of AgNP and test nematodes. The initial studies on the toxicity of AgNP involved free-living species Caenorhabditis elegans (Roh et al, 2009;Meyer et al, 2010) and Panagrellus redivivus (Mahmoud et al, 2016). Oxidative stress-related PMK-1 P38 MAPK activation was reported as a mechanism for toxicity of AgNP to Caenorhabditis elegans (Lim et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…AgNPs have shown potent antimicrobial effects in countering E. coli, S. aureus and S. marcescens [130][131][132] . It also showed antinematode 133 , antiviral 134 , anticancer 135,136 and anti-inflammatory effects 137 . Aqueous P. emblica fruit extract when evaluated against eight pathogenic cultures and its applicability in green synthesis of AgNPs showed that all the test cultures were inhibited by the AgNPs and the average ZOI measured 19.25±2.7 mm 129 .…”
Section: Amla: Antimicrobial Nanoparticlesmentioning
confidence: 99%